IDENTIFIKASI PERUBAHAN JASA LINGKUNGAN DENGAN MENGGUNAKAN PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS DI BOGOR - Azar Rachdian; Lilik Budi Prasetyo; Siti Badriyah Rushayati (Media Konservasi, 2016)
Environmental services are the services provided by the ecosystem functions that have direct and indirect benefits to human well being. The purpose of this study is to analyze environmental services changes in the District and City of Bogor on 1990 and 2014. The focus of the study is analyzing the environmental service of carbon stock, carbon sinks, biodiversity, the aesthetic of landscape, water regulation and climate amelioration. The data collection method began with data preprocessing then followed by a groundcheck at field to take sample point, after that followed by image classification that produce land cover. Land cover that has been classified then given the value of environmental services by changing the format of raster into a polygon. The average value of environmental services in District of Bogor on 1990 is 4,86 and in the city of Bogor is 4,56, while on 2014 the average value of environmental services in District of Bogor is 4,54 and in the City of Bogor is 3,72. Change of environmental services in the City of Bogor greater than in District of Bogor due to the magnitude of changes in land cover types of forest to other land cover especially for settlement. Beside that, it is also caused by differences of development policy between Bogor district and city of Bogor. The focus of development in the district is agricultural production sector and the city are trading and services sectors. Government of City and Distric of Bogor should do some efforts for maintaining and even improving environmental services by allocating space for land which dominated by trees and agroforestry system.Keywords: environmental services, environmental services score, environmental services change